Pemberian Biochar Sekam Padi Terhadap Pertumbuhan dan Hasil Padi (Oryza Sativa L.) Sawah Irigasi Teknis - Wahyuni Lestari; Aryunis Aryunis; Akmal Akmal (Jurnal Agroecotania : Publikasi Nasional Ilmu Budidaya Pertanian, 2022)
Rice plant (Oryza sativa L.) is the staple food crop of almost all Indonesians. In line with the increase in population from year to year, the need for rice also continues to increase. Therefore, efforts to increase production must continue. On the other hand, the decline in land area due to the conversion of functions from agricultural land to non-agricultural land also causes reduced production. However, in several regions the government has also printed new rice fields, which are generally not on fertile land. Therefore, efforts to increase production through improved farming or intensification, such as the application of new technological developments, need to be done. The aim of this study was to obtain the best dose in administering rice husk biochar for growth and yield of technically irrigated rice fields (Oryza sativa L.). The research was carried out in the Rice Fields of Rawa Medang Village, Batang Asam District, West Tanjung Jabung Regency, Jambi Province which lasted for 5 months, starting from December 26, 2019 to April 19, 2020. The experimental design used was a randomized block design (RAK). Provision of rice husk biochar at several dose levels, namely p0 = without rice husk biochar (300 kg Urea + 100 kg KCl + 100 kg SP-36), p1 = 5 tons ha-1 rice husk biochar + 1⁄2 dose of urea + 1⁄2 dose of KCl + 1⁄2 dose SP-36, p2 = 10 tonnes ha-1 rice husk biochar + 1⁄2 dose of urea +1⁄2doseofKCl+1⁄2doseofSP-36,p3 =15tonnesofha-1 biocharofricehusk+1⁄2doseofurea+ 1⁄2doseofKCl+1⁄2doseofSP-36,p4 =20tonsha-1 ricehuskbiochar+1⁄2doseofurea+1⁄2doseof KCl+1⁄2doseofSP-36,p5 =25tonsha-1 ofricehuskbiochar+1⁄2doseofurea+1⁄2doseofKCl+1⁄2 dose of SP-36. The variables observed were plant height, maximum number of tillers, number of productive tillers, panicle length, number of grains per panicle, percentage of empty grain per panicle, dry grain yield and weight of 1000 grains of grain. The results showed that giving bochar of rice husk had an effect and could increase the growth and yield of rice plants. Provision of 5 tonnes of rice husk biochar ha-1 to 25 tonnes ha-1 increased the yield of the maximum number of tillers, the number of productive tillers, and the yield of milled dry unhulled rice. Provision of rice husk biochar 25 ton ha-1 gave the best effect on lowland rice plants.